The Range of Application of Domestic Antiviral Drug in Рediatrics - O. V. Shamsheva; O. V. Molochkova (Детские инфекции (Москва), 2015)
The article presents the results of studies of the effectiveness and safety of domestic antiviral drug Аrbidol in children. Arbidol demonstrated antiviral activity not only against influenza viruses, and other respiratory viruses (respiratory syncytial virus, parainfluenza, rhinovirus), coronavirus, rotavirus, and others.